Effects of Pleurotus pulmonarius (Fr.) quel on cholesterol level, muscle contractility, tissue condition and serum metabolomic profile in Hypercholesterolemic-Induced Rats / Noor Fazila Mohamed Yahaya - Noor Fazila , Mohamed Yahaya (2021)
Cardiovascular disease is one of the leading factors of mortality worldwide and one of the risks that contributes to the disease is hypercholesterolemia. Statins have been widely prescribed as the solution to hypercholesterolemic patients after a better lifestyle practice failed to improve the total cholesterol level. However, contraindication and drug-drug interaction always jeopardize the patients to various health risks. Thus, nutraceutical or functional food received overwhelming reception from the society. Pleurotus pulmonarius or commonly called grey oyster mushroom is one of the best culinary mushrooms with great taste and texture. Besides, its tremendous benefits have been verified through various scientific findings. As an extended effort to explore more of its hidden benefits, this study focused on in vivo observations on the rats. The crude aqueous extract (CA) had been verified in a previous study as potent free radical scavenging activity in vitro, making it a suitable candidate to be studied furthered in vivo by using forty-eight Wistar-Kyoto rats. The extract was subjected to tissue integrity test; analysis on their ability to dilate a pre-constricted thoracic aortic ring. CA was able to dilate the thoracic aortic ring by 60 % and also protected the thoracic aortic tissue when concomitantly fed to hypercholesterolemic-induced rats. The higher dose of CA (2.0 g/kg body weight) fed to the rats also assisted the thoracic aortic ring to dilate when challenged with phenylephrine at the percentage of 43.11 %, followed by 34.17 % for simvastatin and finally 12.51 % for low dose CA (0.5 g/kg body weight). Besides its ability to protect thoracic aortic tissue, histopathology observations proved CA was able to contribute to the liver tissue viability in the hypercholesterolemic-induced rats. Metabolomic analysis was also performed to observe the metabolites involved in the selected rat’s sera. Metabolites levels including serotonin, L-formylkynurenine, pantothenic acid, phosphodimethylethanolamine and 5-hydroxyquinoline were altered in the sera samples. Each of the metabolite plays its own role in the pathogenesis chain by either contributing to disease progression or improvises the viability of the rats. It can be concluded that CA from P. pulmonarius was able to ameliorate the disease progression due to high cholesterol. This study also suggested that CA works best as preventive agent rather than curative as it not able to fully restore the structure of damaged tissues following hypercholesterolemic state.